THE INFLUENCE OF ACOUSTIC BAFFLES OF NOISE BARRIERS ON THE NOISE LEVEL OF TRAFFIC - Figlus, Tomasz; Wilk, Andrzej; Liscak, Stefan; Gozdek, Lukasz (Doprava a spoje, 2012)
This article deals with an issue of influence of acoustic baffles of noise barriers on the noise level of traffic because the noise has become the global danger for the environment at last years. In this article, there are described the measures method of acoustic baffle on the noise barrier effectiveness and the results of made measurement.